Principles of Teaching Grammar in CLT - Xusanova Sharofatxon Isroilovna; Qosimova Inobatxon Qadirjanovna (Researchparks Publishing, 2022)
The aim of the article is to analyze the different ways of teaching grammar in communicative language teaching and find innovative methods which can be effective in the EFL classrooms. Communicative grammar is based on the communicative approach to the teaching of foreign languages. Grammar must not be taught in isolation but it should be integrated to the four skills of language: listening, speaking, reading and writing. Teaching grammar should be based on context. In this article given information about various teaching techniques which in corporate communicative grammar and advantages and disadvantages of applying them.